2011
DOI: 10.1088/1748-0221/6/07/p07007
|View full text |Cite
|
Sign up to set email alerts
|

Neutron/gamma discrimination properties of composite scintillation detectors

Abstract: A composite scintillator is a solid solution, which contains the grains of organic molecular single crystal introduced into a polymer matrix and placed inside the housing. Hereunder, we present n/γ discrimination properties of four composite scintillators; two of the them are based on p-terphenyl and two others-on stilbene. The results obtained with a stilbene single crystal and a liquid scintillator BC501A are shown as a comparison. Initial conclusion, which is drawn from the paper, is that composite scintill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…Emission wavelengths of anthracene, stilbene, and p-terphenyl were 445-525, 400-500, and 350-450 nm, respectively. These emission wavelengths were consistent with previous literatures [2,9] and emission wavelengths were same as those under UV excitation (photoluminescence). Fig.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Emission wavelengths of anthracene, stilbene, and p-terphenyl were 445-525, 400-500, and 350-450 nm, respectively. These emission wavelengths were consistent with previous literatures [2,9] and emission wavelengths were same as those under UV excitation (photoluminescence). Fig.…”
Section: Resultssupporting
confidence: 93%
“…As a result, FOM of anthracene, stilbene, and p-terphenyl were 1.53, 1.10, and 1.26, respectively. Similar plots but with different definition of FOM were examined by many groups [9,[15][16][17][18] and to our knowledge all evaluations are essentially equal. In one of the recent reports, Iwanowska et al [9] reported PSD capabilities of stilbene and p-terphenyl based organic scintillators and they concluded that p-terphenyl based one was better.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the gamma-ray spectrum of the composite stilbene scintillator as shown in Figure 9 (b), it is difficult to accurately determine the Compton edge location from the neutron spectrum due to a poor energy resolution. In this study, the peak location was determined by a Gaussian fit resulting in a large uncertainty [17]. The composite stilbene scintillator and the singlecrystal stilbene scintillator showed good energy linearity, as seen in Figure 13.…”
Section: Performance Evaluation Withmentioning
confidence: 98%
“…In many cases, radiation monitoring requires the counting of a signal from a first radiation source within an interference signal induced by a second particle emitter, namely α/β vs. γ; n vs. γ, γ vs. γ … The most efficient techniques consist in the recognition of the particle origin associated with each individual pulse event by coincidence/anti-coincidence, pulse height discrimination (PHD) or pulse shape discrimination (PSD) [16]. However, event-by-event discrimination techniques may be found unreliable in particular mixed field configurations.…”
Section: Compensation Measurementmentioning
confidence: 99%